Ardl دراسة تطبيقية لأثر الشيخوخة الديمغرافية على صندوق التقاعد الجزائري باستخدام منهجية - مفتاح,فايزة (University of Eloued جامعة الوادي, 2025)
نهدف من خلال هذه الدراسة التطبيقية إلى دراسة المتغيرات الديمغرافية التي تضعف نظام التقاعد الجزائري، عن طريق التحديد التجريبي للآثار المترتبة عن شيخوخة السكان على صندوق التقاعد الجزائري. حيث قمنا ببناء نموذجين للانحدار يشرحان العلاقة بين فئة السكان اللذين يشكلون نظام التقاعد (المساهمين والمتقاعدين) والمتغيرات الديموغرافية التي تحدد الشيخوخة، وذلك باستعمال البرنامج الإحصائي إفيوز الإصدار التاسع (Eviews9) لتقدير واختيار الأنموذج الملائم لهذه الدراسة. أكدت النتائج التجريبية أن الارتفاع في أمل الحياة والانخفاض في معدلات الوفيات يؤديان إلى زيادة عدد المتقاعدين، كما أن الانخفاض في معدلات المواليد يؤدي إلى انخفاض في عدد المساهمين، مما يؤدي بنظام التقاعد الجزائري للعمال الأجراء إلى وضع غير مستقر. Abstract: Through this applied study, we aim to study the demographic variables that weaken Algeria's retirement system by empirically identifying the effects of population ageing on the Algerian Pension Fund. We have built two regression models that explain the relationship between the population that makes up the retirement system (contributors and retirees) and the demographic variables that determine ageing, using the statistical program Eviews9 to estimate and select the appropriate model for this study. The empirical results confirmed that the rise in life expectancy and the decline in mortality rates are leading to an increase in the number of retirees, and that the decline in birth rates is leading to a decline in the number of contributors, leading the Algerian retirement system for wage workers to an unstable situation.
Keywords: نظام التقاعد; شيخوخة السكان; متوسط العمر المتوقع; معدلات الوفيات; معدلات الخصوبة; Retirement system; population ageing; life expectancy; mortality rates; fertility rates